The Influence of Moral Obligation, Religiosity, and Attitude on Crowdfunding Donation Intention - Ryan Rahmat Febriansyah; Nurfauziah Nurfauziah (Cita konsultindo, 2024)
This study aims to analyze the influence of moral obligation, religiosity, and attitudes on donation intention through crowdfunding platforms. Crowdfunding has become an increasingly popular fundraising method, particularly among the Indonesian community, which tends to have a high level of solidarity. Factors such as moral obligation, levels of religiosity, and individual attitudes are considered to play an important role in influencing a person’s decision to donate. The research method used is a quantitative approach with data collection through a survey distributed to 163 respondents who have either donated or are interested in donating through crowdfunding, and data analysis was conducted using PLS-SEM. The collected data were then analyzed using multiple linear regression techniques to examine the relationships between moral obligation, religiosity, attitudes, and donation intention. The results show that moral obligation and religiosity have a significant impact on donation intention, while attitudes also play an important role but with a more moderate influence.